POWDERY MILDEW RESISTENT4-dependent cell wall deposition is a consequence but not the cause of temperature-induced autoimmunity. (14th September 2021) - Hessler, Giuliana; Portheine, Stephan M; Gerlach, Eva-Maria; Lienemann, Tim; Koch, Gerald; Voigt, Christian A; Hoth, Stefan
Abstract : Cell wall deposition generally occurs in Arabidopsis autoimmunity and depends on reduced temperature. Duration of low temperature treatment correlates with a point of no return in autoimmunity. Abstract: Plants possess a well-balanced immune system that is required for defense against pathogen infections. In autoimmune mutants or necrotic crosses, an intrinsic temperature-dependent imbalance leads to constitutive immune activation, resulting in severe damage or even death of plants. Recently, cell wall deposition was described as one of the symptoms following induction of the autoimmune phenotype in Arabidopsis saul1-1 mutants. However, the regulation and function of this deposition remained unclear. Here, we show that cell wall deposits, containing lignin and callose, were a common autoimmune feature and occurred in proportion to the severity of the autoimmune phenotype at reduced ambient temperatures. When plants were exposed to reduced temperature for periods insufficient to induce an autoimmune phenotype, the cell wall deposits were not present. After low temperature intervals, sufficient to induce autoimmune responses, cell wall deposits correlated with a point of no return in saul1-1 autoimmunity. Although cell wall deposition was largely abolished in saul1-1 pmr4-1 double mutants lacking SAUL1 and the callose synthase gene GSL5/PMR4, their phenotype remained unchanged compared with that of the saul1-1 single mutant. Our data showed that cell wall deposition generally occurs in autoimmunity, but appears not to be the cause of autoimmune phenotypes.